APLIKASI GOOD GOVERNACE PEMERINTAH KECAMATAN DI KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Sujendra, Bima (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2017)
Applications Good Governace District Government Rasau In District Kubu Raya Jaya selected researchers are encouraged by the phenomenon is still not maximal implementation of good governance in Sub Rasau Jaya, it's still not expected because of the implementation of the principles of good governance right. To that end, the general problem of research formulated: